Implementation of Cooperative Script Learning in an Effort to Improve Thematic Learning Outcomes Theme 3 Daily Tasks Subtheme 1 my Daily Tasks at Home in Grade II Students of MI Negeri 3 Jakarta Academic Year 2022/2023 - Rochmani Rochmani (International Journal Labs, 2023)
This study used three rounds of action research. Each round consists of four stages, namely: design, activity and observation, reflection, and revision. The target of this study was Grade II, students. The data obtained are in the form of formative test results, and observation sheets for teaching and learning activities. This research is based on the following problems: (a) Does Cooperative Script affect Thematic learning outcomes in Grade II Students? (b) How high is the level of mastery of Thematic subject matter in Grade II Students? The objectives of this study are: (a) To uncover the influence of Cooperative Script on Thematic learning outcomes in Grade II Students. (b) Want to know how far the understanding and mastery of Thematic subjects in Grade II Students is. From the results of the analysts, it was found that student learning achievement increased from cycle I to cycle III, namely, cycle I (64%), cycle II (78%), and cycle III (100%). The conclusion of this study is that the Cooperative Script method can have a positive effect on the learning motivation of Grade II Students and this learning model can be used as an alternative Thematic Theme 2 Events in Life Sub Theme 1 Various Events in Life.